ST Segment Elevation - Lucaci Laurențiu (Sciendo, 2022)
As the earliest indirect sign of an acute coronary occlusion arriving against non-operative collateral heart vessels, the unabating ST segment elevation accounts for the acute coronary syndrome asking for mandatory and immediate reperfusion therapy. The geography of the ST segment elevations usually enables one to identify the culprit artery and to guess its likely occlusion site, as pivotal pieces of the necessary vital risk forecasting, along with somehow expected occurring arrhythmias. Aside from the classical ST segment elevation myocardial infarction (STEMI) pattern, a handful of distinctive non-ST elevation appearances of the acute coronary occlusion also need imperative reperfusion therapy, thus qualifying themselves as STEMI equivalents. The early forthcoming of ST elevation during an acute transmural ischaemic episode, as well as the wide availability of the electrocardiogram, make it an invaluable diagnostic tool. Yet many confounding factors are able to limit the diagnostic sensibility of ST elevation (as for example its customary absence in the conventional leads in some cases of circumflex artery occlusion, or the casual mutual cancellation of the transmural ST vectors from opposite ventricular walls), the accuracy of the electrocardiographic localisation of the occlusion site (due to coronary anatomic variants, concomitant new or old coronary lesions elsewhere, previous coronary artery bypass grafts), as well as its specificity for transmural ischaemia (by virtue of a well-known manifold of non-ischaemic causes). While the STEMI patient must be offered undelayed reperfusion therapy, the non-ischaemic ST elevation one should be kept away from the haemorrhagic risk of a useless invasive procedure.